ANALYSIS OF MATHEMATICAL LITERACY SKILLS OF STUDENTS IN CLASS VIII SMP NEGERI 3 DAMPELAS IN SOLVING GEOMETRY PROBLEMS IN TERMS OF VAN HIELE LEVEL. - Rahmayani, Risti; Sukayasa, Sukayasa; Ismaimuza, Dasa; Meinarni, Welli (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research is a descriptive qualitative research that aims to analyze the mathematical literacy skills of SMP Negeri 3 Dampelas students in solving geometry problems in terms of Van Hiele levels. Subjects were selected based on the Van Hiele Geometry Test (VHGT) results by considering the subject teacher's suggestions. Data were collected using tests. The test instrument was prepared based on indicators of mathematical literacy skills and has met the valid criteria. The results of this study show that Van Hiele level 0 thinking subjects can only fulfill 2 indicators of mathematical literacy skills, the subject is able to write the known and asked and can change the problem in the problem. Van Hiele level 1 thinking subjects were able to fulfill 3 indicators of mathematical literacy skills, the subject was able to write down what was known and asked and could relate to the concept of beam area with information from known data to produce a plan to solve the problem using the formula correctly. The level 2 Van Hiele thinking subject was able to fulfill 4 indicators of mathematical literacy skills, the subject was able to write the known and questioned, write the formula to be used correctly, was able to connect with the concept of beam area then apply his knowledge of surface area and provide an explanation of the steps to solve the problem.